Acute Drought Is an Important Driver of Bark Beetle Infestation in Austrian Norway Spruce Stands - Netherer, Sigrid; Panassiti, Bernd; Pennerstorfer, Josef; Matthews, Bradley (Frontiers in Forests and Global Change, 2019)
Infestations of Norway spruce by the Eurasian spruce bark beetle Ips typographus have recently caused peaks in salvaged timber in Central European forests. Apart from extensive breeding material due to abiotic disturbance, increased spring and summer temperatures as well as precipitation deficits are presumably key drivers of bark beetle population dynamics. In this study, we investigated the influence of effective temperature sums, chronic and acute drought stress, and stand characteristics for explaining salvage logging due to bark beetle attack in Norway spruce stands of Austrian Federal Forests. We retrospectively simulated temperature and transpiration deficit as drought proxy by use of the monitoring tool PHENIPS-TDEF, a well-proven bark beetle phenology model, combined with an additional hydrological module developed for simulating transpiration deficits (TDEF) in forest stands. Overall, we found that bark beetle infestation occurred more frequently in stands with high share of Norway spruce, increased stand age and stand density. The probability of ongoing attacks was significantly higher in stands subject to salvage logging in the previous year. Chronically dry forest stands described in the forest inventory database as growing on shallow, xeric, and low moisture soil conditions, were significantly less prone to bark beetle attack across all forest enterprises. However, acute drought indicated by stand transpiration deficits was a significant predictor of bark beetle attacks, especially in stands geographically located in warmer and drier areas of the country. Although importance of TDEF parameters differed with geographic location and observation period, the clear increase in attacks across all forest stands in 2015 was principally linked to previous year’s and actual summer transpiration deficits. We conclude from our results that in the absence of severe abiotic disturbance a combination of ample host availability, favorable temperature conditions for bark beetle development, and acute disposition of trees to attack caused by drought stress can intensify population growth and very likely lead to bark beetle mass outbreaks.